2019
DOI: 10.1590/0004-282x20190030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional, amplitude-integrated and geodesic sensor net EEG used in premature neonates: a systematic review

Abstract: The use of methods to evaluate cortical activity in neonates has great importance in modern medicine, as it allows the observation and evaluation of several clinical aspects, which guarantees that the health team has knowledge about possible intervention measures that may be necessary in the treatment of newborns. Objective: This systematic review aimed to compare the main technologies available for the evaluation of brain functions in neonates, among them: the conventional electroencephalogram (EEG), the amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Imaging examinations are of great significance in the diagnosis and evaluation of brain damage in preterm infants [6]. Although both head color Doppler ultrasound and MRI have predictive value for poor neurological prognosis of preterm infants, there are still some preterm infants with neurodevelopmental disorders and imaging examinations did not find brain injury changes.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging examinations are of great significance in the diagnosis and evaluation of brain damage in preterm infants [6]. Although both head color Doppler ultrasound and MRI have predictive value for poor neurological prognosis of preterm infants, there are still some preterm infants with neurodevelopmental disorders and imaging examinations did not find brain injury changes.…”
Section: Introductionmentioning
confidence: 99%
“…The brain function signal develops to reflect a primarily discontinuous EEG pattern early in life with functional maturation to more continuous signal as the infant approaches term gestation [8]. Sousa et al [9] revealed that electrographic seizures observed in the first week of life could be related to adverse outcomes that could affect the neonate in the future.…”
Section: Discussionmentioning
confidence: 99%